Dory Fantasmagory - Hanlon, Abby (Hanlon, Abby. Dory Fantasmagory, 2014)
Dory, the youngest in her family, is a girl with a very active imagination, and she spends the summer playing with her imaginary friend, pretending to be a dog, battling monsters, and generally driving her family nuts.